STABILITY OF CHLOROQUINE PHOSPHATE TABLETS INOCULATED W lTH BACTERIA L SPECIES (Biological Sciences - PJSIR, 2003)
Five popular brands of chloroquine tablets available to the average Nigerian consumers were examined for the effects of Staphylococcus aureus and Bacillus cereus, on the dissolution , disintegration and  hardness  after six  weeks  of incubation. The maximum percent dissolution was 98.34 % with Bacillus subtiliswhile the minimum was 19.12% with Staphylococcus aureus. The disintegration results showed a maximum of 69 min. 19 sec with Staphylococcus aureus while  the least  was 56  sec with Bacillus subtilis. The maximum hardness obtained was 12.75 kg and the least was 1 .25kg also with Staphylococcus aureus. The dissolution, disintegration and hardness also varied with the control. The metabolic activities  of the  bacterial  species were believed to have caused the variations in the  physical  properties  of  the  chloroquine  phosphate  tablets.  The results from this investigation strongly advises adequate  storage of chloroquine  phosphate  tablets, especially  when  it is the  drug of choice  for the  treatment  of  malaria  in  most  endemic  countries of sub-Saharan  Africa.